Leadership: Communicating Strategically in the 21st Century - Suffian Hadi, Ayub; Norhayati Abd, Manaf; Mohammad Rezal, Hamzah (2014)
This paper seeks to discuss the functions of communication in ensuring effective leadership in the 21st century organization. The definition concept of leadership often intertwines and this provides various dimensions which create challenges to define leadership which encompasses all traits. Further, this paper later expanded from concept and definitions of leadership to leadership communication models. This paper recommended that leadership is about setting direction and aligning people to desired direction. Significantly, future leaders must be able to ensure that the subordinates are treated as members of the organization, whereby consistency in providing sound leadership would determine employee motivation and performance.